SWOT Analysis of Classic Vocal Learning at The Medan Flow Music Course Institution - Riau Wika; Vanesia Amelia Sebayang; Muhizar Muchtar (International Journal Labs, 2023)
Classical vocals still have a special place in the hearts of music fans despite the complexity of learning them. The presence of music course institutions has an important role in shaping students to become skilled in the field of classical vocals. Based on this, this research aims to determine classical vocal learning strategies at the Flow Music course institution. The theories used in this research are SWOT analysis theory, learning methods, and classical vocals. The data sources in this research consist of primary sources, namely classical vocal instructors and students, while secondary sources consist of information obtained by other people or other sources previously. The data collection techniques used in the research were observation, interviews, and documentation. The research results show that the classical vocal learning strategy at the Flow Music course institution was identified from internal strengths and weaknesses as well as external opportunities and threats with the strategy results being: 1) Increasing collaboration with schools, arts institutions, and local churches to increase visibility and attract more many students; 2) Applying distance learning technology to reach students from various locations; 3) Conduct active recruitment to address the shortage of instructor quantity; 4) Establish partnerships with related music institutions in more strategic locations; 5) Increase online marketing efforts; 6) Manage finances wisely to overcome the threat of unstable economic conditions; 7) Organizing local music events and competitions involving the participation of students and the general public; 8) Improving service quality through music workshops and collaboration with the local music industry.